The Role of Calculation Model in Experimentally Determining Thermal Energy Generated in Laser Rod of Solid Laser - Thinh, Pham Vu; Anh, Le Ngoc (Communications in Physics, 2014)
In many solid state laser pumped by flash lamps, thermal source distributed in laser rod is heterogeneous, complicated and cannot be described by explicit functions. Pumping process can be considered an adiabatic process. Thermal gradients generated within the laser rod are the result of the inhomogeneous distribution of absorbed energy. Calculation model and numerical method can help to determine the relation between the experimental results and thermal energy generated in laser rod.